Seasonal gonadal changes, spawning and condition index of oyster Crassostrea madrasensis (preston) in the Korampallam creek, Tuticorin - Palaniswamy, Rani (Indian Journal of Fisheries, 2011)
Studies on seasonal changes of the gonad of oysters are useful in spat fall prediction and also in selecting the broodstock for hatchery production of the seed. The gonadal condition of the oysters Crassostrea madrasensis in different seasons was reported by Rao (19S6), Durve (196S), Stephan (1980), Rajapandian and Rajan (1983) and Narasimham (1987). Nair and Mahadevan (1983) elucidated the various aspects in oyster culture carried out in the Tuticorin bay. The present study gives the results on the seasonal changes in the gonad and meat condition of oysters collected from the Korampallam creek, near Tuticorin.